2018
DOI: 10.1093/cid/ciy759
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Hemagglutination-inhibition Antibody Titer as a Mediator of Vaccine-induced Protection for Influenza B

Abstract: The majority of the effect of inactivated influenza vaccination in children is mediated by the increased HAI titer after vaccination, but other components of the immune response to vaccination may also play a role in protection and should be further explored. Causal mediation analysis provides a framework to quantify the role of various mediators of protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 16 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…In comparison, hemagglutination inhibition titer against B/Victoria influenza virus mediated an estimated 57% of inactivated influenza vaccine efficacy against virologically confirmed B/Victoria influenza illness. 44 As hemagglutination inhibition titer has been used to guide vaccine strain selection and approval, this defines a benchmark for a potential level of mediation relevant for supporting vaccine approval decisions. 45 The very high overall vaccine efficacy and the small number of vaccine recipients with negative/undetectable antibody levels in COVE limited the ability to identify a high percentage of neutralization-mediated vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, hemagglutination inhibition titer against B/Victoria influenza virus mediated an estimated 57% of inactivated influenza vaccine efficacy against virologically confirmed B/Victoria influenza illness. 44 As hemagglutination inhibition titer has been used to guide vaccine strain selection and approval, this defines a benchmark for a potential level of mediation relevant for supporting vaccine approval decisions. 45 The very high overall vaccine efficacy and the small number of vaccine recipients with negative/undetectable antibody levels in COVE limited the ability to identify a high percentage of neutralization-mediated vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…These results raise at least two obvious questions: (1) whether conventional haemagglutination inhibition antibody titres, despite their longstanding use as predictors of post-vaccination efficacy against both influenza A and B,15, 26 are truly an appropriate surrogate for an effective humoral response in therapeutic studies against influenza A, and hence whether better markers of antibody-mediated activity might exist that should be substituted, and (2) whether the overall host immune response to infection with influenza B might differ in some fundamental way from that against influenza A. It is known, for example, that acute influenza infection is also associated with pronounced impairment of the cellular immune response, including defective T-cell responses and a sometimes lethal unbridling of the proinflammatory cytokine cascade 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…The HAI assay is a well-established approach to evaluate the ability of inactivated influenza vaccine in clinical protection 13 . Clinical data demonstrated that the magnitude of the HAI titer 4 weeks after vaccination correlated with TLR5 expression upregulation in human subjects 4 .…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, EGCG3”Me is the first orally delivered exogenous compound to upregulate TLR5 expression. EGCG3”Me enhanced the split-virus vaccine-induced HAI titer, a criterion used to evaluate protective effects of vaccines 13 .…”
Section: Discussionmentioning
confidence: 99%